Pembinaan Literasi Organisasi Wanita Katolik Republik Indonesia Cabang Sleman, Yogyakarta - Sinurat, Rina Elysa; Mahamboro, Dionius Bismoko (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
Some of Indonesia’s women’s mass organizations, once pivotal in the nation’s fight for independence, now seem to be losing momentum. Among the challenges they face is a history of policies limiting their activities to the domestic sphere, stifling broader engagement. The Catholic Women of the Republic of Indonesia (WKRI) is one organization determined to break through these constraints. WKRI seeks to revitalize its mission by encouraging its members to engage in public dialogue through writing and other forms of expression. In collaboration with the WKRI Sleman Branch in Yogyakarta, a series of writing workshops, discussions, and reflective activities aim to strengthen members’ voices. This initiative culminates in a commemorative book celebrating WKRI’s 100th anniversary, offering critical reflections on the role of women in public life.